A New strategy for on-line Droop adjustment for Microgrid connected DGs - Sathyaprabakaran B; Subrata Paul; Debashis Chatterjee (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
This paper proposes a simple and effective control technique for interconnection of DG resources to the power grid via interfacing converters based on Phase locked loop (PLL) and Droop control. The behaviour of a Microgrid (MG) system during the transition from islanded mode to grid-connected mode of operation has been studied. A dynamic phase shifted PLL technique is locally designed for generating phase reference of each inverter. The phase angle between filter capacitor voltage vector and d-axis is dynamically adjusted with the change in q-axis inverter current to generate the phase reference of each inverter. During fluctuations in load capacity, the grid-connected system must be able to supply balanced power from the utility grid side and micro-grid side. Therefore, droop control is implemented to maintain a balanced power sharing. The inverter operates in voltage control mode in order to control the filter capacitor voltage. An adjusted droop control method for equivalent load sharing of parallel connected Inverters, without any communication between individual inverters, has been presented. The control loops are tested with aid of MATLAB Simulink tool during several operating conditions.